1984
DOI: 10.2172/5288701
|View full text |Cite
|
Sign up to set email alerts
|

Purex diluent degradation

Abstract: The chemical degradation of normal paraffin hydrocarbon (NPH) diluents both in the pure state and mixed with 30% trlbutyl phosphate (TBP) was investigated in a series of experiments. The results show that degradation of NPH in the TBP-NPH-HNOg system is consistent with the active chemical agent being a radical-like nitrogen dioxide (N0") molecule, not nN0» as such. Spectrophototnetric, gas chromatographic, mass spectrographic, and tltrlmetrtc methods were used to identify the degradation products, which includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…. These combine with actinide and fission product ions forming strong complexes, which decrease the stripping metal recovery and decontamination efficiencies and can sometimes cause physical problems [4]. The NPH diluent degrades to various oxidation and nitration products including long-chain nitro, nitrite, and nitroso hydrocarbons.…”
Section: Niowave 99 Mo U Utilization Processmentioning
confidence: 99%
See 2 more Smart Citations
“…. These combine with actinide and fission product ions forming strong complexes, which decrease the stripping metal recovery and decontamination efficiencies and can sometimes cause physical problems [4]. The NPH diluent degrades to various oxidation and nitration products including long-chain nitro, nitrite, and nitroso hydrocarbons.…”
Section: Niowave 99 Mo U Utilization Processmentioning
confidence: 99%
“…The NPH diluent degrades to various oxidation and nitration products including long-chain nitro, nitrite, and nitroso hydrocarbons. Additional NPH degradation products include alcohols, unsaturated alcohols, nitro alcohols, nitro alkenes, esters, and long-chain organic acids, which tend to affect phase separation and may retain certain short-lived fission products [4,5].…”
Section: Niowave 99 Mo U Utilization Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Khaikin has suggested that HDBP is a stable product resulting from reaction of dissolved oxygen and the TBP radical [9]. The degradation has also been investigated as a function of diluent [12][13][14][15][16], water and nitric acid [17][18][19][20][21], temperature [22,23], and metal ions [20,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The actinides, U and Pu, from the HNO 3 medium, are then preferentially extracted into an organic medium containing 30% (V=V) solution of tri-n-butyl phosphate (TBP) in n-dodecane (n-DD). Incidentally, both TBP and n-DD undergo chemical and radiolytic degradation during fuel reprocessing (1)(2)(3). The accumulations of these products are detrimental to the reprocessing and hence monitoring the organic phase for the accumulation of these degradation products is therefore essential.…”
Section: Introductionmentioning
confidence: 99%